Trusts of imperfect obligation. Issue 4 (8th April 2022) - Wilde, David
Abstract: This article seeks to briefly examine what is known about the so-called 'trusts of imperfect obligation'—valid non-charitable purpose trusts for monuments, animals, and (probably) religious ceremonies. In particular, it considers the suggestions sometimes made that the 'Pettingall order' provides an enforcement mechanism for them, or that they are really 'powers' misclassified as 'trusts'.